Template Synthesis, Spectroscopic Characterization and Antimicrobial Studies of Oxovanadium(IV) Tetraazamacrocyclic Complexes Derived from 1, 8-Diaminonaphthalene and Substituted β-Diketones: Pharmaceutical Science-Chemistry - Kumar, Harikesh; Singh, Ashutosh; Pandey, J .K (International Journal of Life Science and Pharma Research, 2022)
A new series of oxovanadium (IV) tetraazamacrocyclic complexes of type [VO(mac)]SO4, have been synthesized via in situ reaction of 1,8-diaminonaphthalene and substituted β-diketones (1-phenyl-3-(phenyl/4-chlorophenyl/4-hydroxyphenyl/4- methoxyphenyl/4-nitrophenyl)-diketone) in the presence of oxovanadium(IV) sulphate in methanol. Attempts to synthesize the corresponding metal free macrocyclic ligands did not prove successful. Complexes were characterized on the basis of elemental analyses, conductance measurements, magnetic properties and spectral (electronic, IR, and EPR) data. The magnetic moments of the complexes lie in the range 1.70-1.78BM suitable for complexes with one unpaired electron and paramagnetic nature. The infrared spectra indicates that the ligands coordinate through four aza nitrogen atoms to vanadium(IV). The fluid solution EPR spectra show an eight-line pattern typical for a mononuclear VO(IV) complexes. The spectral studies support a square pyramidal geometry for the oxovanadium(IV) complexes. The oxovanadium complexes were tested for their antibacterial activity against bacteria Bacillus subtilis, Staphylococcus aureus, Escherichia coli and antifungal activity against fungi Aspergillus niger and Candida albicans. The complexes show moderate to good activity as compared to standard antibiotic tetracycline and the antifungal drug fluconazole.